2013
DOI: 10.1002/14651858.cd009119.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Chest radiographs for acute lower respiratory tract infections

Abstract: Background Acute lower respiratory tract infections (LRTIs) (e.g. pneumonia) are a major cause of morbidity and mortality and management focuses on early treatment. Chest radiographs (X-rays) are one of the commonly used strategies. Although radiological facilities are easily accessible in high-income countries, access can be limited in low-income countries. The efficacy of chest radiographs as a tool in the management of acute LRTIs has not been determined. Although chest radiographs are used for both diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
2
33
2
1
Order By: Relevance
“…There is minimal utility in obtaining a chest X-ray in the early stages of an acute lower tract infection except to exclude other etiologies of dyspnea. However, early chest X-rays (0-2 days within symptom onset) tend to be normal or demonstrate increased bronchovascular markings [1] . Later stages of the disease tend to be less specific for COVID-19 as secondary complications may look more like pneumonia than a typical viral infection and the role for serial chest X-rays appears to have more utility in establishing a baseline to assess improvement of aeration and ascertain the locations of tubes and lines in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is minimal utility in obtaining a chest X-ray in the early stages of an acute lower tract infection except to exclude other etiologies of dyspnea. However, early chest X-rays (0-2 days within symptom onset) tend to be normal or demonstrate increased bronchovascular markings [1] . Later stages of the disease tend to be less specific for COVID-19 as secondary complications may look more like pneumonia than a typical viral infection and the role for serial chest X-rays appears to have more utility in establishing a baseline to assess improvement of aeration and ascertain the locations of tubes and lines in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there is no evidence of lymphadenopathy or pleural effusions on this chest X-ray. While most patients imaged at 0-2 days after symptom onset had normal imaging, studies have shown limited specificity in diagnosing lower respiratory tract illnesses with chest X-ray [1] .…”
Section: Fig 1 -Respiratory Viral Panel By Pcr Dated March 8 2020: mentioning
confidence: 99%
“…The top 24 global EM articles for 2013 are listed in Table . The complete database of all 434 global EM articles for 2013, as well as full summaries and critical analyses of the top 24 global EM of articles of 2013, can be found in Data Supplements S1 and S2 (available as supporting information in the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Seven years later, she presented to the ED complaining of acute respiratory symptoms compatible with acute bronchitis without alarming features but, nevertheless, a CXR was ordered. Data suggest that CXR for acute cough in most cases is unlikely to affect management or outcome [7,8]. In the absence of alarming features to suggest pneumonia (fever, tachypnea, tachycardia, or findings of consolidation in chest exam), the American College of Chest Physicians recommends against obtaining CXR for acute cough [9].…”
Section: Discussionmentioning
confidence: 99%